Quota Policy and Education as Social Law: A brief report on the implementation of this policy at the Federal Institute of Education, Science and Technology of Santa Catarina (Research, Society and Development, 2021)
Brazilian Higher Education has expanded strongly in recent years and the adoption of public policies for student access and permanence has brought to higher education institutions a high number of students from public schools and in adverse socioeconomic conditions. This Article is the result of a bibliographic investigation on education as a social right and the historical framework of Quotas in Brazil and its legislation, as well as the implementation at the Federal Institute of Education, Science and Technology of Santa Catarina.